Socioeconomic and environmental impacts of biofuels : evidence from developing nations - Gasparatos, Alexandros; Stromberg, Per (Cambridge University Press, 2012)
"Biofuels are currently in the middle of a heated academic and public policy debate. Biofuel production has increased fivefold in the past decade and is expected to double by 2020. Most of this expansion will happen in developing nations. This book is the first of its kind, providing a comprehensive overview of the biofuel debate in developingcountries. The chapters are written by a multidisciplinary team of experts who expose the key drivers and impacts of biofuel production and use. The book covers impacts as diverse as air pollution, biodiversity loss, deforestation,energy security, food security, greenhouse gas emissions, and use change, rural development, water consumption, and other socioeconomic issues. It has a wide geographical focus accommodating examples from countries in Africa, America, and Asia. As such, this book will become an indispensable companion for academics, practitioners, and policy makers who wish to know more about biofuel issues in the developing world."-- Back cover.